LE CAPITAL ET LE CHIFFRE D’AFFAIRE :SONT SYNONYMES OU DEUX CONCEPTS DIFFERENTS PAR L’ENTREPRENARIAT INFORMEL CONGOLAIS OU COMMERÇANTS INFORMELS. - Mendo, Germain Elembo; Mokili, Gabriel Mobondo (IJRDO - Journal of Business Management, 2023)
Our research focuses on how Congolese entrepreneurs of small size or informal beginners digest the two concepts (capital and turnover). Knowledge of products and services bet on the market, allows entrepreneurs to take advantage of the best sales conditions. The belly is an art recognized for a long time, which gave rise to many analyzes, or studies. An effective salesperson (a company) is not only talented, it is someone who has a method in managing the interaction with customers In the analysis of its two concepts (capital and turnover) by Congolese informal entrepreneurs ; Our problem revolves around the following questions :  Do Congolese informal entrepreneurs or informal traders know the difference between capital and turnover ?  Is there a network or communication channel for informal traders to build their capacity.  Do entrepreneurs have a level required to carry out the commercial activity ? Considering the way in which the Congolese State does not manage to create jobs for the population and that unemployment at a higher level, and that survival poses a problem for Congolese daily newspapers ; we put forward the hypotheses according to which, informal merchants are unable to make the difference between capital and turnover, there is no network or communication circuit for their reinforcement of capacity, entrepreneurs have a level required.